Integrated Networks: National and International Online Experiences - Muniz-Solaris, Osvaldo; Coats, Christine (International Review of Research in Open and Distributed Learning, 2009)
There is an increasing impression among online geography educators that interaction can be developed based on specific teaching and learning methods. The authors developed a practical research study to investigate this issue. The study was based on advanced graduate courses in geography at Beijing Normal University and Texas State University. International interaction was complemented by online collaboration among the US local group. Both synchronous and asynchronous communication systems were used, which spanned two platforms. Results of this experience indicate that teaching and learning methods must be enhanced by a flexible online learning model and extensive organizational support in order to increase interaction and reach a certain level of cooperation.